High Expression of Vascular Endothelial Growth Factor Receptor-1 (VEGFR-1) is Highly Correlated with Eclampsia - Lukas, Efendi (Indonesian Socety of Obstetrics and Gynecology, 2012)
Objectives: To understand the expression of placental vascular endothelial growth factor receptor (VEGFR-1) in severe preeclampsia with complication (eclampsia and HELLP syndrome). Methods: The study was an observational study with cross sectional design, performed at several hospitals of Department of Obstetrics and Gynecology Medical Faculty of University of Hasanuddin, Makassar. Subjects met to inclusion criteria were taken as samples. Placental tissue samples were taken from cord insertion site and fixated with formalin buffer solution. Immunohistochemical examination was performed at Center of Research University of Hasanuddin. Antibody used were primary antibody of Mouse monoclonal anti VEGFR-1 antibody (Santa Cruz) dissolved to 1:100 and link antibody (secondary antibody labeled with biotin) (Dakopatt). Placental tissues were examined in Streptavidin biotin peroxides and interpreted according to the intensity of trophoblast cytoplasmic dye. Results: High VEGFR-1 expression was found in 100% of the placenta from patients with eclampsia , 42.9&% in patients with HELLP syndrome and 37.8% in patients with severe preeclampsia. High VEGFR-1 expression was correlated to incidence of eclampsia (p=.000) and not correlated to severe preeclampsia and HELLP syndrome (p=0.734). Conclusion: High VEGFR-1 expression was correlated to eclampsia and not correlate to severe preeclampsia and HELLP syndrome. [Indones J Obstet Gynecol 2012; 36-3:116-20] Keywords: eclampsia, HELLP syndrome, severe preeclampsia, VEGFR-1 expression